Development of Microscopy Apparatus Switchable between Fluorescence and Ultralow-Frequency Raman Modes - Ken Takazawa (Journal of Analytical Methods in Chemistry)
In this study, a microscopy apparatus that can switch between the fluorescence microscopy and ultralow-frequency Raman microscopy modes was developed. The apparatus can be easily constructed by equipping a standard epi-illumination microscope with an additional port featuring a removable half mirror. Owing to the switchability, fluorescence imaging, and spectroscopy, Raman spectroscopy in the frequency range down to ∼10 cm−1 can be performed using the apparatus. To demonstrate the advantageous features of this apparatus, micron-sized crystals of perylene, which have two polymorphic forms, were analyzed. The two polymorphs were clearly identified based on their shapes, fluorescence spectra, and ultralow-frequency Raman spectra, all of which can be observed with our apparatus alone. These results indicate that the apparatus is a powerful tool for the analysis and characterization of various nano-/micron-sized crystals.